Does intra-articular injection of tenoxicam after arthrocentesis heal outcomes of temporomandibular joint osteoarthritis? A randomized clinical trial - Zeynep Bayramoglu; Günay Yapici Yavuz; Aydın Keskinruzgar; Mahmut Koparal; Göksel Simsek Kaya (BMC, 2023)
Abstract Background Temporomandibular joint osteoarthritis (TMJ-OA) is a degenerative disease and manifests itself with pain and limitation of movement in the jaws. Arthrocentesis alone or in combination with intraarticular injections is one of the most commonly used treatment methods in these patients. The aim of the study is to examine the effectiveness of arthrocentesis plus tenoxicam injection and to compare it with arthrocentesis alone in patients with TMJ-OA. Methods Thirty patients with TMJ-OA who were treated randomly with either arthrocentesis plus tenoxicam injection (TX group) or arthrocentesis alone (control group) were examined. Maximum mouth opening (MMO), visual analog scale (VAS) pain values, and joint sounds were the outcome variables, which were evaluated at pre-treatment and at 1, 4, 12, and 24 weeks after treatment. Statistical significance was set at p < 0.05. Results The gender distribution and mean age were not significantly different between the two groups. Pain values (p < 0.001), MMO (p < 0.001), and joint sounds (p < 0.001) improved significantly in both groups. However, there was no significant difference between the groups in terms of outcome variables [pain (p = 0.085), MMO (p = 0.174), joint sounds (p = 0.131)]. Conclusions Arthrocentesis plus tenoxicam injection showed no better outcomes in terms of MMO, pain, and joint sounds compared with arthrocentesis alone in patients with TMJ-OA. Trial registration Injection of Tenoxicam Versus Arthrocentesis Alone in the Treatment of Temporomandibular Joint Osteoarthritis, NCT05497570. Registered 11 May 2022. Retrospectively registered, https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S000CD7A&selectaction=Edit&uid=U0006FC4&ts=6&cx=f3anuq